Partial decarboxylation of hafnium oxide clusters for high resolution lithographic applications. Issue 41 (7th October 2022) - Liao, Pin-Chia; Chen, Po-Hsiung; Tseng, Yu-Fang; Shih, Ting-An; Lin, Ting-An; Gau, Tsi-Sheng; Lin, Burn-Jeng; Chiu, Po-Wen; Liu, Jui-Hsiung
Abstract : Treatment of hafnium clusters Hf6 O4 (OH)4 (RCO2 )12 with LiOH in DCM/H2 O afforded Hf6 O4 (OH)6 (RCO2 )10, using which high resolution EUV lithographic patterns can be achieved. Abstract : This work shows a great influence on the EUV performance of hafnium carboxylate clusters via slight structural modification. Treatment of hexameric hafnium clusters Hf6 O4 (OH)4 (RCO2 )12 (R = i-alkyl) with LiOH in DCM/water (25 °C, 20 min) afforded hafnium clusters formulated as Hf6 O4 (OH)6 (RCO2 )10 according to elemental analysis, NMR data, ESI-Mass and TGA studies. Two representatives 1-OH and 2-OH have been examined via surface characterization, e-beam and EUV lithographic studies. The two photoresists can form smooth and defect-free thin films over a large domain with the surface RMS roughness being smaller than 1.0 nm. For e-beam, patterns are only resolved into 31 nm half-pitch (HP) due to the large shrinkage in the photoresist thickness. With an EUV interference mask, the patterns have been resolved into a 17 nm HP with small line-width roughness (LWR) at similar dose energies. The XPS studies of the EUV exposed film of sample 1-OH revealed a decomposition of five carboxylate ligands even at high energy doses.